Self-assembled monolayers with distributed dipole moments originating from bipyrimidine units - Gärtner, Michael; Sauter, Eric; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
The concept of distributed dipoles in molecular self-assembly on solid substrates was tested for the example of thiolate self-assembled monolayers (SAMs) on Au(111) containing dipolar 2,5′-bipyrimidine units. These were attached to a thiol anchoring group either directly or via a phenylene-methylene spacer, with the spacer decoupling the dipolar moiety from the substrate and promoting layer formation. As expected, the SAMs containing the spacer groups exhibited a higher quality, including a higher packing density and nearly upright molecular orientation. The electrostatic effects of the dipolar bipyrimidine moieties were tested through C 1s and N 1s photoemission spectra, where electrostatic core-level shifts impact the shapes of the spectra. Additionally, changing the orientation of the dipoles allows a variation of the work function over a range of ∼1.35 eV. The experiments were complemented by density-functional theory calculations. The work function tuning range was reasonably high, but smaller than expected considering that for SAMs with a single embedded pyrimidine group per molecule work function changes already amounted to ∼1.0 eV. This behavior is rooted in an asymmetry of the studied SAMs: For dipoles pointing away from the substrate, the expected doubling of the work function change between monopyrimidine and bipyrimidine SAMs essentially occurs. Conversely, for the downward-oriented pyrimidine dipoles, the second polar ring has hardly any effect. Consistent observations were made for the core-level shifts. We discuss several factors, which are potentially responsible for this asymmetry, like disorder, depolarization, or Fermi-level pinning. Of these, the most likely explanation is the adsorption of airborne contaminants interacting with the nitrogen atoms in the immediate vicinity of the outer surface. These are present only in films with downward oriented dipoles. In spite of these complications, some of the introduced distributed dipole SAMs serve as important model systems for understanding electrostatic effects at interfaces. They are also of interest for controlling carrier-injection barriers in organic (opto) electronic devices.